THE IMPACT OF PERCEIVED VALUE, DESTINATION SERVICE QUALITY AND TOURIST SATISFACTION ON DESTINATION LOYALTY AMONG INTERNATIONAL TOURISTS VISITING MALAYSIA - Mahadzirah Mohamad; Nur Izzati Ab Ghani; Muhamad Nasyat Muhamad Nasir, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The competitive situation and challenges within the tourism industry worldwide entailed a better understanding of destination loyalty’s determinants in achieving Malaysia’s aspiration to retain its international reputation as one of the most desirable tourist destinations in Asia. Literature proved that factors such as perceived value, service quality and tourist satisfaction could influence in improving destination loyalty. In view of this, there is a need to examine the influence of several constructs namely perceived value, service quality and tourist satisfaction that can contribute to the loyalty of international tourists towards Malaysia as it was suggested in the literature review. Therefore, the main objectives of this study were to examine the influence of perceived value and service quality on tourist satisfaction, which in turn would influence destination loyalty. In this study, tourist satisfaction was treated as the mediating variable. The proposed model was tested using structural equation modeling on a sample of 337 foreign tourists selected using random sampling method. The study was conducted from August 2014 to October 2014. The proposed model achieved acceptable goodness-of-fit. The requirements for reliability and validity were also met. The results of the empirical study indicated that perceived value influenced tourist satisfaction and destination loyalty. In addition, the findings revealed that service quality had a significant effect on satisfaction. However, service quality had no significant effect on destination loyalty. Moreover, the findings indicated that tourist satisfaction had a full mediating effect on the relationship between service quality and destination loyalty. The study contributed to a better understanding of behavioral factors that would represent a sustainable source for increasing customer retention at the level of individual providers as well as a destination as a whole. Individual providers should focus on delivering quality services related to accommodation, information and facilities, health and hygiene, and shopping that were associated with the visitor’s travel experience. Aspects of perceived value identified in the study could be used as a strategic tool in managing tourism offerings which could enhance the destination’s competitive edge.